(untitled) (International Journal of Scientific Research in Science and Technology, 2025)
This study investigates the performance of a large multiuser multiple-input multiple-output (MU-MIMO) millimeter-wave (mmWave) communication system in an underground mine environment using a base station equipped with 128 antennas. The analysis is based on channel measurements conducted at 28 GHz, where a virtual antenna array at the base station serves multiple users. Key channel parameters, including large-scale path loss, temporal dispersion, coherence bandwidth, and sum-rate capacity, are examined and evaluated. The findings indicate that a multislope path loss model provides a more accurate representation of path loss across different propagation segments within the mining gallery. The time dispersion analysis reveals that 90% of the root-mean-square (RMS) delay spreads are below 4 ns, suggesting minimal time dispersion in the underground mine channel. Additionally, the results demonstrate that the RMS delay spread remains independent of the propagation distance. The sum-rate capacity analysis highlights the potential of massive MIMO technology in enhancing spectral efficiency. The study shows that the achievable capacity can reach up to 33.54 bit/s/Hz with eight active users. The unique characteristics of deep mine environments, such as rich scattering and irregular topology, are also discussed. These results provide valuable insights into the propagation behaviour of mmWave channels in underground mines, contributing to the optimization of wireless communication systems in such challenging environments.